Frontiers of Higher Order Fuzzy Sets 2014
DOI: 10.1007/978-1-4614-3442-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Time-Series Forecasting via Complex Fuzzy Logic

Abstract: Adaptive neuro-complex-fuzzy inference system (ANCFIS) is a neurofuzzy system that employs complex fuzzy sets for time-series forecasting. One of the particular advantages of this architecture is that each input to the network is a windowed segment of the time series, rather than a single lag as in most other neural networks. This allows ANCFIS to predict even chaotic time series very accurately, using a small number of rules. Some recent findings, however, indicate that published results on ANCFIS are subopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Their experimental results have demonstrated that the ANCFIS based approach was more accurate in predicting power output on a simulated solar cell. Additionally, in a recent paper Yazdanbaksh et al presented a recommended approach to determining input windows that balances the accuracy and computation time [77].…”
Section: Applications Of Cfl/cfsmentioning
confidence: 99%
“…Their experimental results have demonstrated that the ANCFIS based approach was more accurate in predicting power output on a simulated solar cell. Additionally, in a recent paper Yazdanbaksh et al presented a recommended approach to determining input windows that balances the accuracy and computation time [77].…”
Section: Applications Of Cfl/cfsmentioning
confidence: 99%
“…Finding d allows us to get an optimal level of autocorrelation within each delay vector (by taking each successive value, or every second, every third, etc.) [45]. d is determined heuristically, guided by taking the first minimum of the time-delayed mutual information statistic [42].…”
Section: Data Preprocessingmentioning
confidence: 99%
“…While, Alkouri and Salleh [3] proposed the notions of linguistic variable, hedges and several distances on CFS. Yazdanbakhsh and Dick [4] proposed time-series forecasting via complex fuzzy logic and a systematic review of CFS. Recently, Bi et al [5] proposed complex fuzzy geometric aggregation operators.…”
Section: Introductionmentioning
confidence: 99%
“…To precisely cope with such kind of problems, Yager [22] proposed the framework of q-rung orthopair fuzzy set (q-ROFS) whose restriction is that the sum of q-power of membership and q-power of non-membership grade is belonging to [0,1]. Obviously, the q-ROFS can describe effectively such kinds of information, i.e., 0.9 4 + 0.7 4 = 0.7 + 0.24 = 0.94 ≤ 1. The FS, IFS, and PFS all are the special cases of q-ROFS, this characteristic makes q-ROFS more general than existing FSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation